2012
DOI: 10.1021/ja3094372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of B-Heterocyclic π-Radical and Its Reactivity as a Boryl Radical

Abstract: The first isolation and full characterization of the stable, persistent diazaboracyclic neutral radical 3 is reported. Reduction of base-stabilized difluororoborane 2 provided radical 3 as a neutral molecule having a planar sp(2) boron atom attached to one fluorine and two nitrogen atoms. ESR spectroscopy and DFT calculations indicated that the unpaired electron is delocalized over the six-membered ring. Because of an electronic transition related to the singly occupied molecular orbital, 3 has a characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 33 publications
4
49
0
2
Order By: Relevance
“…In this case, however, the spin density localizeda tt he borona tom seems to be considerably lower. [29] Furthermore the theoretical study also showed close similarity of both SOMOso f(Bab-Dipp)C and (Bab-tBu)C ( Figure 6).…”
Section: Photo-induced Hc(sp 3 )àC(sp 3 )H Bondcleavage In Bis(1h-21supporting
confidence: 53%
See 1 more Smart Citation
“…In this case, however, the spin density localizeda tt he borona tom seems to be considerably lower. [29] Furthermore the theoretical study also showed close similarity of both SOMOso f(Bab-Dipp)C and (Bab-tBu)C ( Figure 6).…”
Section: Photo-induced Hc(sp 3 )àC(sp 3 )H Bondcleavage In Bis(1h-21supporting
confidence: 53%
“…is Nozaki's persistent N,N ‐stabilized neutral boron radical. In this case, however, the spin density localized at the boron atom seems to be considerably lower . Furthermore the theoretical study also showed close similarity of both SOMOs of (Bab‐Dipp) .…”
Section: Resultsmentioning
confidence: 60%
“…In 2013, Roesky and co‐workers found that silyl‐substituted CAACs yielded the radicals 32 a – c , which were stable under inert atmosphere . Utilizing steric bulk and nitrogen‐derived electronic effects, Yamashita, Nozaki, and co‐workers prepared the heterocyclic radical 33 with 7π electrons . This radical was best described as an allylic radical but reacted with benzoquinone and benzoyl peroxide at the boron atom.…”
Section: Radicals Based On Electron Push And/or Pull Systemsmentioning
confidence: 99%
“…An X‐ray diffraction study revealed the dicationic property of 3 , in which two diazadiborinine units are bridged through the B−O bonds of the para ‐OC 6 H 4 O linker. Although similar B−O bond‐forming reactions between neutral and anionic boron radicals and benzoquinone or benzoyl peroxide have been described previously, to the best of our knowledge, this result is the first example of boron‐centered radical reactivity of cationic boron radicals.…”
Section: Figurementioning
confidence: 99%